Stability of smooth and rough mini-implants: clinical and biomechanical evaluation - an in vivostudy - Vilani,Giselle Naback Lemes (2015)
Objective: To compare in vivo orthodontic mini-implants (MI) of smooth (machined) and rough (acid etched) surfaces, assessing primary and secondary stability.Methods:Thirty-six (36) MI were inserted in the mandibles of six (6) dogs. Each animal received six (6) MI. In the right hemiarch, three (3) MI without surface treatment (smooth) were inserted, whereas in the left hemiarch, another three (3) MI with acid etched surfaces (rough) were inserted. The two distal MI in each hemiarch received an immediate load of 1.0 N for 16 weeks, whereas the MI in the mesial extremity was not subject to loading. Stability was measured by insertion and removal torque, initial and final mobility and by inter mini-implant distance.Results:There was no statistical behavioral difference between smooth and rough MI. High insertion torque and reduced initial mobility were observed in all groups, as well as a reduction in removal torques in comparison with insertion torque. Rough MI presented higher removal torque and lower final mobility in comparison to smooth MI. MI did not remain static, with displacement of rough MI being smaller in comparison with smooth MI, but with no statistical difference.Conclusions:MI primary stability was greater than stability measured at removal. There was no difference in stability between smooth and rough MI when assessing mobility, displacement and insertion as well as removal torques.